IMPLEMENTASI APLIKASI PENGINPUTAN INVENTORY MENGGUNAKAN METODE AGILE BERBASIS WEB - Tampubolon, Dumayanti; Simanjuntak, Pastima (Computer Science and Industrial Engineering, 2023)
The process of collecting manual input data info Microsoft Exel takes a long time, data management cannot be done by several warehouse admins at the same time, making inventory reports is often not on time from schedule because they have to recapitulate goods receipt data and goods expenditure data, submit inventory reports to the department takes a long time, data management errors often occur in entering data, deleting data. Microsoft Excel also cannot store data and information centrally in a database, so there is often a discrepancy between the information obtained and data loss caused by human error. Agile development methods are a methodology in software development that is based on an iterative process consisting of rules and agreed solutions. With the aim to produce a software that has a high selling value but uses the lowest possible manufacturing costs. So as to obtain research results in the form of applications built for inventory input systems, namely with web-based agile methods.